2022
DOI: 10.1177/15586898221120566
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mixed Methods Using Active Learning Approaches

Abstract: There is a paucity of empirical research on teaching mixed methods. To fill this gap in literature, this convergent mixed methods study explores the effectiveness of using active learning approaches in teaching a mixed methods course. The qualitative data, including 10 individual interviews, 29 students’ reflections, and 26 teaching evaluation surveys, were used to examine students’ learning experience and outcomes. Students’ presentations ( N = 29) and final papers ( N = 29) were transformed into numbers as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Despite the expansion of the literature on MMR pedagogy, there remains a need for continuous efforts to provide empirical evidence on MMR course design, implementation, and evaluation (e.g., Frels et al, 2014; Hou, 2021; Onwuegbuzie et al, 2011; Zhou, 2023). Additionally, given the complex nature of MMR pedagogy, its exploration necessitates the use of socio-ecological frameworks, which in turn require a thorough comprehension of research processes, contents, contexts, and the interactions of these elements (Ivankova & Plano Clark, 2018).…”
Section: Identifying the Key Challenges In Mmr Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the expansion of the literature on MMR pedagogy, there remains a need for continuous efforts to provide empirical evidence on MMR course design, implementation, and evaluation (e.g., Frels et al, 2014; Hou, 2021; Onwuegbuzie et al, 2011; Zhou, 2023). Additionally, given the complex nature of MMR pedagogy, its exploration necessitates the use of socio-ecological frameworks, which in turn require a thorough comprehension of research processes, contents, contexts, and the interactions of these elements (Ivankova & Plano Clark, 2018).…”
Section: Identifying the Key Challenges In Mmr Teachingmentioning
confidence: 99%
“…Consequently, the collaborative reading of an MMR article, combined with the engagement in challenging tasks under the instructor’s guidance, can significantly reduce learning obstacles and enhance the comprehension of MMR (Greenwood & Terry, 2012). MMR pedagogy research recently empirically demonstrated the effectiveness of active discussions among students in addressing difficult tasks in MMR learning (Hou, 2021; Zhou, 2023).…”
Section: Examining Mike’s Treasure Hunt Workhop Using Vygotsky’s Soci...mentioning
confidence: 99%
“…In the third article, Zhou (2023), with an affiliation in education, focused on teaching mixed methods. The author conducted a convergent mixed methods study to explore the effectiveness of using active learning approaches in a mixed methods course.…”
Section: In This Issuementioning
confidence: 99%
“…In fact, a large majority of graduate students complain that their research methods courses inadequately prepared them for independent research. (p. 119) When investigating the best practices of teaching research methods, the literature points to transformative, active learning pedagogies (Allen & Baughman, 2016;Gunn, 2017;Lundahl, 2008;Zhou, 2022), yet many instructors continue to follow a traditional, teacher-directed approach (Kilburn et al, 2014). Caution is given against teaching research methods courses using simplistic approaches, as ineffective teaching using a linear process "poses the danger of [students] adhering to strict methodological prescriptions with little regard for varying contexts or sensitivity to emergent research problems" (Preissle & Roulston, 2016, p. 13).…”
Section: Reinvention Of the Eddmentioning
confidence: 99%